Systematic review and meta-analysis of the diagnostic value of optokinetic after-nystagmus in vestibular disorders - Reynders, Marie; Van der Sypt, Lynn; Bos, Jelte; Cools, Wilfried; Topsakal, Vedat (Frontiers in Neurology, 2024)
Introduction To date, no systematic review or meta-analysis has critically evaluated the relevance of using optokinetic after-nystagmus (OKAN) in diagnosis of vestibular disorders. To assess the role of OKAN in diagnosis of vestibular disorders. The OKAN time constant (TC) between patients with vestibular disorders and healthy participants will be compared. Methods Automated search strategies were carried out in the Embase, Medline PubMed, Web of Science, and Scopus databases from inception to December 2023. The following inclusion criteria were applied: 1) evaluation of OKAN in individuals with vestibular disorders, 2) clinical trials, and 3) inclusion of healthy individuals as the control group. Exclusion criteria were: 1) animal studies, 2) non-clinical trial study designs, 3) assessment of non-vestibular disorders, 4) no examination of OKAN TC, 5) only examination of healthy participants, 6) studies published in a language other than English, 7) no healthy participants as control group, 8) case reports, and 9) only abstract available. The random-effects model was used to pool the data. The Joanna Briggs Institute (JBI) Critical Appraisal Tools was used to assess the risk of bias. The quality assessment was performed with the aid of the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies, provided by NHLBI. The PRISMA guidelines were used as reporting guidelines. The main outcome of this study was the between-group mean difference (MDbetween) in OKAN TC and its 95% confidence interval between patients with vestibular disorders and healthy participants. Results: Seven out of 244 screened articles were included that studied 289 participants. The overall mean difference (MD=-7.08) with a 95% CI of [-10.18;-3.97] was significant (p=0.014). The heterogeneity was significant (p=0.02). Quality assessment was generally good (76%). The risk of bias was low in five studies and moderate in two studies. Conclusion: The results demonstrate that OKAN TC is significantly shorter in patients with vestibular disorders compared to healthy controls. This finding is important for future research, particularly with the emergence of novel clinical tools and diagnostic syndromes.